2014
DOI: 10.19030/ajee.v5i1.8610
|View full text |Cite
|
Sign up to set email alerts
|

From Knowing-About To Knowing-To: Development Of Engineering Pedagogical Content Knowledge By Elementary Teachers Through Perceived Learning And Implementing Difficulties

Abstract: The present study sought to reveal how elementary teachers develop their engineering pedagogical content knowledge (PCK) after leaving professional development programs to practice engineering teaching in real classroom settings. Participants of this study were the elementary teachers who received one-week training of engineering education provided by EfF (a P-12 Engineering teaching and learning institute in a Midwestern university). Data of this study were collected from these elementary teachers through fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…Just as considerations of organizational culture can help explain corporate autonomy dilemmas, teaching beliefs may be considered in discussing school autonomy in school–university–industry partnerships. Engineering pedagogical content knowledge (Sun & Strobel, 2014) requires not only knowledge of engineering but also knowledge of how to apply instructional methods and translating that engineering content to the appropriate grade level; the latter is a noted challenge in the teacher–industry partnership literature (Buxner et al, 2014). It may be intimidating for an educator with low teaching engineering self‐efficacy (Yoon et al, 2014) to participate in this project.…”
Section: Discussionmentioning
confidence: 99%
“…Just as considerations of organizational culture can help explain corporate autonomy dilemmas, teaching beliefs may be considered in discussing school autonomy in school–university–industry partnerships. Engineering pedagogical content knowledge (Sun & Strobel, 2014) requires not only knowledge of engineering but also knowledge of how to apply instructional methods and translating that engineering content to the appropriate grade level; the latter is a noted challenge in the teacher–industry partnership literature (Buxner et al, 2014). It may be intimidating for an educator with low teaching engineering self‐efficacy (Yoon et al, 2014) to participate in this project.…”
Section: Discussionmentioning
confidence: 99%
“…When the literature examined, it is seen that in recent years, scale development studies in the fields of PCK and TPCK (Technological Pedagogical Content Knowledge) for teachers and pre-service teachers are frequently used (Graham et al, 2009;Schmidt et al, 2009;Landry, 2010;Marks, 1990;Sun & Strobel, 2014). However, when the literature was examined, a limited number of studies were found that measure the Pedagogical Content Knowledge of teachers and pre-service teachers towards STEM (Rigelman, 2014;Yildirim & Sahin-Topalcengiz, 2019).…”
Section: Determining the Needmentioning
confidence: 99%
“…Teachers' comfort with open-ended activities, engineering concepts, curriculum outside of state standards, and their relationship with peers or administrators can all impact the ability to successfully engage in the collaboration. In the literature on science content knowledge, researchers found a positive link between teaching science self-efficacy and content knowledge (Menon and Sadler, 2016), but the same cannot be said about the engineering education literature (Sun and Strobel, 2014). There is something about engineering in particular, that seems to have decreased the perceived capacity to contribute to the collaboration for teachers and some did explicitly state they were afraid of looking unintelligent in front of their engineering partners or students.…”
Section: Capacity-building Metrics (Goal 2)mentioning
confidence: 99%